Greater Well-Being in More Physically Active Cancer Patients Who Are Enrolled in Supportive Care Services. (May 2020) - Tristão Parra, Maíra; Esmeaeli, Naghmeh; Kohn, Jordan; Henry, Brook L.; Klagholz, Stephen; Jain, Shamini; Pruitt, Christopher; Vicario, Daniel; Jonas, Wayne; Mills, Paul J.
Background: Cancers are one of the leading causes of mortality worldwide. Cancer patients are increasingly seeking integrative care clinics to promote their health and well-being during and after treatment.Aim: To examine relationships between physical activity (PA) and quality of life (QoL) in a sample of cancer patients enrolling in integrative care in a supportive care clinic. Also, to explore circulating inflammatory biomarkers and heart rate variability (HRV) in relationship to PA and QoL.Methods: A cross-sectional design of adult patients who sought care in the InspireHealth clinic, Vancouver, British Columbia, Canada. Patients with complete PA data (n = 118) answered psychosocial questionnaires, provided blood samples, and received HRV recordings before enrollment. Patients were stratified into "less" versus "more" active groups according to PA guidelines (150 minutes of moderate or 75 minutes of vigorous PA or an equivalent combination).Results: Breast (33.1%) and prostate (10.2%) cancers were the most prevalent primary diagnoses. Patients engaging in more PA reported better physical ( U = 1265.5, P = .013), functional ( U = 1306.5, P = .024), and general QoL ( U = 1341, P = .039), less fatigue ( U = 1268, P = .014), fewer physical cancer-related symptoms ( U = 2.338, P = .021), and less general distress ( U = 2.061, P = .021). Between PA groups, type of primary cancer diagnosis differed (χ 2 = 41.79, P = .014), while stages of cancer did not (χ 2 = 3.95, P = .412). Fewer patients reported depressed mood within the more active group (χ 2 = 6.131, P = .047). More active patients were also less likely to have ever used tobacco (χ 2 = 7.41, P = .025) and used fewer nutritional supplements (χ 2 = 39.74, P ≤ .001). An inflammatory biomarker index was negatively correlated with vigorous PA ( r s = −0.215, P = .022). Multivariable linear regression ( R 2 = 0.71) revealed that age (β = 0.22; P = .001), fatigue (β = −0.43; P ≤ .001), anxiety (β = −0.14; P = .048), and social support (β = 0.38; P = .001) were significant correlates of QoL.